Respuesta :

Answer: x=12

Step-by-step explanation:

Answer:

  x=1

Step-by-step explanation:

The equation can be simplified and solved using the rules of exponents and the usual inverse operations.

__

Interpreted according to the Order of Operations, your equation is ...

  ((2^2)x)^3 = 64

  (4x)^3 = 64x^3 = 64 . . . . . . use (ab)^c = (a^c)(b^c)

  x^3 = 1 . . . . . . . . . . . . . . divide by 64

  x = ∛1 = 1

__

Perhaps you want x in the exponent:

  (2^(2x))^3 = 64

  2^(6x) = 2^6 . . . . . . . . . use (a^b)^c = a^(bc)

  6x = 6 . . . . . . . . match exponents

  x = 1 . . . . . . divide by 6

_____

Additional comment

Folks are often not careful about identifying exponents. It is helpful if you write the exponent in a way that leaves no ambiguity.